IMPROVING STUDENTS’ VOCABULARY MASTERY IN READING BY USING EXTENSIVE READING AT SMK SINAR HUSNI 2 BM - Agusdiani Purba; Reni Rosianna Lumban Gaol (Universitas Potensi Utama, 2021)
The aimed of this research was to find out improvement of the students’ vocabulary by Extensive Reading at SMK 2 BM Sinar Husni. This research was a classroom action research. It consisted of two cycles. The procedure research in every cycle consisting of four stage. They planned, act, observed, and contemplating. The subject of research consisted of 30 students from XI SMK Sinar Husni. Post test results in cycle1 there are 8 or 27% of students' who pass through KKM, next to do post test 2 authors give a short story different from cycle1 called